STOCHASTIC QUANTIZATION AND 1/N EXPANSION - Brunelli, J. C.; Mendes, R. S. (World Scientific Publ Co Pte Ltd, 1993)
We study the 1/N expansion of field theories in the stochastic quantization method of Parisi and Wu using the supersymmetric functional approach. This formulation provides a systematic procedure to implement the 1/N expansion which resembles the ones used in the equilibrium. The 1/N perturbation theory for the nonlinear sigma-model in two dimensions is worked out as an example.